LEALDADE DOS CONSUMIDORES NA COMPRA DE ELETROELETRÔNICOS DA CIDADE DE SANTA ROSA/RS - KREUTZ, CARLA R.; NEUBERGER, ENELISE R.; RHODEN, CRISTIANE; TRENTIN, JAQUELINE T.; ZAMBERLAN, LUCIANO (Salão do Conhecimento, 2013)
Resumo